Promocja Polski na międzynarodowym rynku turystycznym - Nawrocka, Elżbieta (The Promotion of Poland at an International Tourism Market, 2005)
The promotion of Poland at an international arena is carried out by many institutions, among others by the Ministry of Culture, the Ministry of Foreign Affairs, the Ministry of Economy and the Polish Tourist Organization. The hereby article presents the diagnosis of promotional activities, POT, at the foreign markets, as well as the comparative analysis of defined aspects of promotional activities , referring to the selected National Tourist Organizations in Europe. So far, no consistent system (comprising an overall concept, coordination and control, transparent division of competencies and responsibilities within the framework of the carried out activities, as well as financing mechanisms) has been constructed, which would account for marketing communication in Poland, as an attractive country at the international tourism market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 201-210